Missing a Nurse Visit - Jonas Lau-Jensen Hirani; Hans Henrik Sievertsen; Miriam Wüst (Institute of Labor Economics (IZA), 2020)
While a large literature studies the impact of exposure to early-life investment policies, this paper examines the impact of changes within a program, the Danish nurse home visiting program, on child and maternal health. We exploit variation induced by a nurse strike, which resulted in families missing one of the four universally-provided nurse visit. Using variation in children's age at strike start, we show that early, but not later, strike exposure increases child and mother contacts to health professionals in the first four years after birth. Forgoing an early nurse visit also increases the probability of maternal contacts to mental health specialists in the first four years after childbirth. We highlight two potential channels for these results: screening and information provision. We show that–in non-strike years–nurses perform well in detecting maternal mental health risks during early visits, and that effects of early strike exposure are strongest for families that we expect to benefit most from information provided by nurses shortly after birth. A stylized calculation confirms that short-run health benefits from early universal home visiting outweigh costs.
Keywords: I11; I12; I14; I18; I21; 330; early-life health; early interventions; nurse home visiting; parental investments